Is the Cranial and Posterior Screw of the "Inverted Triangle" Configuration for Femoral Neck Fractures Safe?. Issue 7 (July 2019) - Hoffmann, Jacob C.; Kellam, James; Kumaravel, Manickam; Clark, Kurt; Routt, Milton L. "Chip"; Gary, Joshua L.
Abstract : Objectives: To determine the frequency where a posterior and cranial screw in a femoral neck that appeared contained on fluoroscopy violates the cortex. Methods: Ten specimens including the hemipelvis with the proximal femur were obtained from unidentified embalmed specimens that were to be cremated after an institutional review board waiver was granted. Under fluoroscopy, the posterior and cranial screw of the inverted triangle configuration for the femoral neck was placed using standard technique with a cannulated 6.5-mm screw. Anterior–posterior and lateral images of the final screw placement were blinded to 2 orthopaedic traumatologists and 1 musculoskeletal radiologist who were asked to determine whether the screw radiographically breached the posterior and cranial cortex. Cadavers were stripped of soft tissues and inspected for screw perforation. Screws were grouped as contained, thread extrusion, or core extrusion. Results: Reviewers classified all 10 screws as radiographically contained within the femoral neck. Cadavers were inspected and found to show: 4 of 10 with core extrusion, 3 of 10 with thread extrusion, and 3 of 10 screws contained within the femoral neck. Conclusions: Seventy percent of screws that were judged to be radiographically contained had cortical breach near the area where the lateral epiphyseal vessels enter the femoral neck. We urge caution against placement of posterior-cranial implants with fluoroscopy alone even if they appear radiographically contained.